PID controller application on cutting tool vibration in milling process - Mohd Faizol Hafiz, Ab Majid (2012)
The control system was used to suppress vibration chatter from machining process. Dynamic and mathematically model had derived from the one degree of freedom (1DOF) for the cutting tool. Control system that been used in this project was passive system and active system. The passive system used to show the instability system and active system had been introduces to control the system. The PID(proportionalintegral-derivative) was been used in this project.. To complete the active system, linear actuator had been used to counter the vibration occur. The simulation had been run using MATLAB/SIMIJLINK software. Comparative study had been done between passive and active control system. From comparative study, PID showed an effectiveness result that suppresses vibration during machining process. PID produced small error compare to passive system (uncontrolled system). PID control was found suitable in control system for machining.